Secondary battery and electric device

By designing a specific carbon-based material structure in the negative electrode sheet of the secondary battery, the problem of difficulty in taking into account both the dynamic performance and the energy density of the secondary battery in the prior art is solved, and the improvement of dynamic performance and energy density is achieved.

CN119852482AActive Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311643955.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-30
Publication Date
2025-04-18
Estimated Expiration
2043-11-30

AI Technical Summary

Technical Problem

When improving the dynamic performance of existing secondary batteries, it is difficult to take into account high energy density and good cycling performance.

Method used

By designing a specific first carbon-based material and a second carbon-based material structure in the negative electrode film layer of the negative electrode sheet, the first carbon-based material is arranged in the first region of the negative electrode film layer and the second carbon-based material is arranged in the second region to improve the dynamic performance of the secondary battery.

Benefits of technology

It achieves improvement in the dynamic performance of the secondary battery, while taking into account high energy density and good circulation performance, extending the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852482A_ABST
    Figure CN119852482A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and an electric device. The secondary battery comprises a negative electrode piece, the negative electrode piece comprises a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer is provided with a first surface away from the negative electrode current collector and a second surface opposite to the first surface, and the thickness of the negative electrode film layer is marked as H; wherein the area from the first surface of the negative electrode film layer to the thickness range of 0.3 H is marked as a first area and comprises a first negative electrode active material, the first negative electrode active material comprises a first carbon-based material, and the first carbon-based material meets the condition that the total pore area S1 of the outer area is smaller than the total pore area S2 of the inner area. The secondary battery has improved dynamic performance, and the volume distribution particle size Dv50 of the first carbon-based material is less than or equal to 15 [mu] m. The secondary battery has improved dynamic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and an electrical device. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As the application scope of secondary batteries becomes wider and wider, people have put forward severe challenges to the performance of secondary batteries. For example, for electric equipment, the fast charge and discharge performance of secondary batteries is becoming increasingly important. Therefore, secondary batteries are required to have better dynamic performance. Summary of the invention

[0003] The present application is made in view of the above-mentioned problems, and its purpose is to provide a secondary battery and an electric device, wherein the secondary battery has improved dynamic performance.

[0004] In order to achieve the above-mentioned object, the first aspect of the present application provides a secondary battery. The secondary battery comprises a negative electrode plate, the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer has a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, and the thickness of the negative electrode film layer is recorded as H;

[0005] Among them, the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the first area of ​​the negative electrode film layer, the first area includes a first negative electrode active material, the first negative electrode active material includes a first carbon-based material, the volume distribution particle size Dv50 of the first carbon-based material is recorded as D, the first carbon-based material includes an external area and an internal area located inside the external area, the external area refers to the area extending from the particle surface of the first carbon-based material to the inside of the particle by a distance of 0.25D, in the cross-sectional view of the first carbon-based material, the total pore area of ​​the external area is recorded as S1, and the total pore area of ​​the internal area is recorded as S2, then the first carbon-based material satisfies S2>S1, and the volume distribution particle size Dv50 of the first carbon-based material is less than or equal to 15μm.

[0006] In the present application, when the first carbon-based material defined above is arranged at least on the side of the negative electrode film layer of the negative electrode plate away from the negative electrode current collector, the kinetic characteristics of the first carbon-based material can be exerted, thereby improving the kinetic performance of the secondary battery.

[0007] According to some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is 7 μm-13 μm. When the volume distribution particle size Dv50 of the first carbon-based material is within the above range, it is further beneficial to improve the dynamic performance of the secondary battery.

[0008] According to some embodiments, the first carbon-based material satisfies 1.5≤S2 / S1≤500, optionally, 2.5≤S2 / S1≤450.

[0009] According to some embodiments, the area of ​​the pore structure in the outer region of the first carbon-based material is less than or equal to 0.15 μm 2 , can be selected to be less than or equal to 0.13μm 2 ; and / or, the inner region of the first carbon-based material includes one or more pores with an area greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of ​​0.15-2.00 μm 2 The pore structure of the first carbon-based material particles having the above structure has a denser structure than the internal area. In this way, on the one hand, the compaction density of the negative electrode film layer can be improved, thereby improving the energy density of the secondary battery; on the other hand, sufficient and stable expansion space can be reserved for the volume change of the first carbon-based material particles, reducing the risk of breakage of the first carbon-based material particles, reducing the electrolyte from entering the particles, thereby reducing the occurrence of side reactions and the consumption of active ions, thereby further improving the storage performance of the secondary battery, and on the other hand, the compaction density of the negative electrode film layer can also be improved.

[0010] According to some embodiments, at least part of the surface of the first carbon-based material has a carbon coating layer. When at least part of the surface of the first carbon-based material has a carbon coating layer, the dynamic performance of the secondary battery can be effectively improved. According to some embodiments, the entire surface of the first carbon-based material has a carbon coating layer.

[0011] According to some embodiments, the first carbon-based material includes primary particles. Optionally, the primary particles account for ≥ 80% of the first carbon-based material. When the first carbon-based material is mainly in the form of primary particles, it is beneficial to the kinetic performance of the secondary battery.

[0012] According to some embodiments, the area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the second area of ​​the negative electrode film layer, the second area is arranged between the negative electrode current collector and the first area, the second area includes a second negative electrode active material, and the second negative electrode active material includes a second carbon-based material. In the embodiment, the second area of ​​the negative electrode film layer is close to the negative electrode current collector. Arranging a second carbon-based material different from the first carbon-based material in this area will not significantly affect the kinetic performance of the secondary battery, and can also improve other secondary properties, such as energy density, by virtue of the characteristics of the second carbon-based material.

[0013] Optionally, the second carbon-based material includes artificial graphite. When the artificial graphite is arranged at least in the second area, it will not have a significant effect on the dynamic performance of the secondary battery, and at the same time, because the artificial graphite has a good powder compaction density, it can improve the capacity density of the secondary battery. In addition, due to the cold-pressed and easily deformed characteristics of artificial graphite, when it is arranged in the lower layer of the negative electrode film layer, it can effectively reduce the rolling pressure of the pole piece and reduce damage to the carbon-based material, which is beneficial to the cycle life of the secondary battery.

[0014] According to some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is smaller than the volume distribution particle size Dv50 of the second carbon-based material. Optionally, the volume distribution particle size Dv50 of the second carbon-based material is 13μm-19μm, and further optionally 14μm-18μm. When the second carbon-based material has a larger particle size than the first carbon-based material, the powder compaction density can be increased, thereby increasing the compaction density difference between the upper and lower layers of the negative electrode membrane and improving the dynamic performance of the secondary battery.

[0015] According to some embodiments, the powder compaction density of the second carbon-based material under a pressure of 50000N is 1.80g / cm 3 -2.05g / cm 3 , optional 1.85g / cm 3 -2.03g / cm 3 The compaction density of the second carbon-based material powder is within the above range, which is beneficial to improving the energy density of the secondary battery.

[0016] According to some embodiments, the surface of the second carbon-based material does not have a coating layer. The second carbon-based material is disposed in the second region of the negative electrode film layer close to the negative electrode current collector. If a coating layer is disposed on the surface of the second carbon-based material, it will affect the powder compaction density, so not having a coating layer is more beneficial to the energy density of the secondary battery.

[0017] According to some embodiments, the second carbon-based material includes artificial graphite of secondary particles. Optionally, the amount of artificial graphite of the secondary particles in the second carbon-based material accounts for greater than or equal to 80%. When the second carbon-based material includes secondary particles, compared to using it only in the form of primary particles, the isotropy of the negative electrode sheet can be improved, thereby further benefiting the dynamic performance of the secondary battery. In particular, when the second carbon-based material is mainly in the form of secondary particles, the dynamic performance of the secondary battery can be improved.

[0018] According to some embodiments, the particle size distribution of the second carbon-based material satisfies (Dv90-Dv10) / Dv50≤1.25, which can be 0.90-1.25. When the particle size distribution of the second carbon-based material is narrow, it is beneficial to improve the energy density of the secondary battery while taking into account the dynamic performance.

[0019] According to some embodiments, the gram capacity of the first carbon-based material is greater than the gram capacity of the second carbon-based material. Optionally, the gram capacity of the first carbon-based material is ≥355mAh / g, which can be 355mAh / g-368mAh / g. Optionally, the gram capacity of the second carbon-based material is 350mAh / g-365mAh / g, which can be 352mAh / g-362mAh / g. The higher gram capacity of the first carbon-based material and the second carbon-based material can jointly improve the energy density of the secondary battery.

[0020] According to some embodiments, the graphitization degree of the first carbon-based material is ≥95.0%, optionally 95.5%-98.0%; and / or the graphitization degree of the second carbon-based material is 90.0%-95.5%, optionally 92.0%-95.5%. The higher graphitization degree of the two materials is conducive to improving the energy density of the secondary battery.

[0021] According to some embodiments, the specific surface area of ​​the first carbon-based material is 1.0 m 2 / g-2.8m 2 / g, optional 1.3m 2 / g-2.1m 2 / g; and / or, the specific surface area of ​​the second carbon-based material is 0.8m 2 / g-2.0m 2 / g, optional 1.1m 2 / g-1.7m 2 / g. A specific surface area within a suitable range is beneficial to the kinetic performance of the secondary battery.

[0022] According to some embodiments, the first carbon-based material satisfies at least one of the following:

[0023] (1) The first carbon-based material satisfies: (Dv90-Dv10) / Dv50≤1.40, which can be 0.90-1.40;

[0024] (2) The powder compaction density of the first carbon-based material under a pressure of 50,000 N is 1.75 g / cm 3 -2.00g / cm 3 , optional 1.80g / cm 3 -1.98g / cm 3 ;

[0025] (3) The tap density of the first carbon-based material is 0.90-1.30 g / cm 3 , optionally 0.95-1.25g / cm 3 ;

[0026] (4) The volume distribution particle size Dv90 of the first carbon-based material is 13 μm-30 μm, optionally 16 μm-23 μm.

[0027] According to some embodiments, the second carbon-based material satisfies at least one of the following:

[0028] (1) The tap density of the second carbon-based material is 0.85-1.25 g / cm 3 , optional: 0.90-1.15g / cm 3 ;

[0029] (2) The second carbon-based material satisfies 0.050≤I D / I G ≤0.300, optionally, 0.070≤I D / I G ≤0.200, I D Indicates that the Raman spectrum is at 1350±50cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±50cm -1 The G peak intensity at .

[0030] According to some embodiments, the first negative electrode active material and / or the second negative electrode active material also include a silicon-based material; optionally, the mass proportion of the first negative electrode active material is less than or equal to 10%, optionally 5%-10%, and / or the mass proportion of the second negative electrode active material is less than or equal to 10%, optionally 5%-10%.

[0031] According to some embodiments, the negative electrode film layer satisfies at least one of the following:

[0032] (1) The compaction density of the negative electrode film layer is ≤1.85 g / cm3 , optionally 1.45-1.75 g / cm 3 ;

[0033] (2) The porosity of the negative electrode film layer is 18.0%-38.0%, optionally 19.0%-34.0%;

[0034] (3) The OI value of the negative electrode film layer is ≤30.0, and can be optionally 8.0-23.0;

[0035] (4) The thickness of the negative electrode film layer is ≥40 μm, and can be optionally 40 μm-140 μm.

[0036] The second aspect of the present application provides an electric device. The electric device comprises any one of the secondary batteries in the above embodiments. When the electric device comprises the secondary battery with improved dynamic performance, it can be charged at a faster speed. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a schematic diagram of an implementation of the negative electrode plate of the present application.

[0038] Figure 2 is a schematic diagram of a cross-sectional image of particles of the first carbon-based material of the present application.

[0039] Figure 3 This is an ion polishing cross-sectional (CP) diagram of one embodiment of the first carbon-based material of the present application.

[0040] Figure 4 A schematic diagram of an implementation of the negative electrode plate of the present application.

[0041] Figure 5 It is a schematic diagram of another embodiment of the negative electrode plate of the present application.

[0042] Figure 6 It is a schematic diagram of another embodiment of the negative electrode plate of the present application.

[0043] Figure 7 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0044] Figure 8 yes Figure 7 An exploded view of a battery cell according to an embodiment of the present application is shown.

[0045] Fig. 9 is a schematic diagram of a battery module according to an embodiment of the present application.

[0046] Fig.10 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0047] Fig.11 yes Fig.10 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0048] Fig.12 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0049] Description of reference numerals:

[0050] 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly; 10 negative electrode plate; 101 negative electrode current collector; 102 negative electrode film layer; 102a first surface; 102b second surface; 1021 first region; 1022 second region; 1023 middle region; 200 first carbon-based material; 201 external region; 202 internal region. DETAILED DESCRIPTION

[0051] Below, the embodiments of the secondary battery and the electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0052] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0053] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0054] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0055] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0056] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.

[0057] If not otherwise specified, the values ​​of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.

[0058] If not otherwise specified, in the present application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.

[0059] With the widespread use of secondary batteries, higher requirements are placed on the charging speed of secondary batteries, that is, the kinetic performance. However, the key to improving the kinetic performance of secondary batteries, especially the fast charging performance, lies in improving the kinetic performance of the negative electrode by reducing the surface density of the negative electrode film layer or reducing the compaction density of the negative electrode film layer. However, a large number of studies have shown that the above methods of improving the kinetics of the negative electrode only improve the kinetic performance of the battery to a certain extent, while the energy density of the secondary battery will be significantly reduced.

[0060] Therefore, it is difficult for current secondary batteries to achieve both high energy density and improved dynamic performance.

[0061] In view of this, a first aspect of the embodiments of the present application provides a secondary battery. The secondary battery improves the dynamic performance of the secondary battery by designing the negative electrode plate. According to a further embodiment, the secondary battery also has a good energy density.

[0062] The term “secondary battery” mentioned herein refers to a battery cell, a battery module or a battery pack.

[0063] Generally, a secondary battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0064] [Negative electrode]

[0065] The secondary battery of the present application includes a negative electrode plate, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer has a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, and the thickness of the negative electrode film layer is recorded as H; wherein, the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the first area of ​​the negative electrode film layer, the first area includes a first negative electrode active material, the first negative electrode active material includes a first carbon-based material, the volume distribution particle size Dv50 of the first carbon-based material is recorded as D, the first carbon-based material includes an external area and an internal area located inside the external area, the external area refers to an area extending from the particle surface of the first carbon-based material to the inside of the particle by a distance of 0.25D, in the cross-sectional view of the first carbon-based material, the total pore area of ​​the external area is recorded as S1, and the total pore area of ​​the internal area is recorded as S2, then the first carbon-based material satisfies S2>S1, and the volume distribution particle size Dv50 of the first carbon-based material is less than or equal to 15μm.

[0066] See also Figure 1 , which shows a schematic diagram of an embodiment of the negative electrode sheet of the present application. Figure 1 As shown, in the embodiment, the negative electrode sheet 10 includes a negative electrode current collector 101 and a negative electrode film layer 102 formed on at least one surface of the negative electrode current collector 101. The negative electrode film layer 102 has a first surface 102a away from the negative electrode current collector 101 and a second surface 102b arranged opposite to the first surface 102a. The thickness of the negative electrode film layer 102 is recorded as H. The area within the thickness range from the second surface 102b of the negative electrode film layer to 0.3H is recorded as the first area 1021 of the negative electrode film layer. The negative electrode film layer area within the thickness range of 0.7H outside the first area 1021 is recorded as the remaining area 1020. The thickness H of the negative electrode film layer refers to the thickness of the negative electrode film layer located on a single side of the negative electrode current collector.

[0067] It should be understood that in the embodiment shown in the figure, the second surface 102b contacts the upper surface of the negative electrode current collector 101, but the structure of the negative electrode plate of the present application is not limited thereto. For example, there may be an additional layer between the negative electrode film layer 102 and the negative electrode current collector 101. In this case, the second surface 102b does not directly contact the negative electrode current collector 101.

[0068] In the embodiment, the first carbon-based material is arranged in the first region 1021 of the negative electrode film layer. According to some embodiments, at least one negative electrode active material different from the first carbon-based material is arranged in at least part of the remaining region 1020. Exemplarily, an additional negative electrode active material (e.g., an additional carbon-based material) is arranged in at least part of the remaining region 1020. Exemplarily, the first carbon-based material also exists in at least part of the remaining region 1020 adjacent to the first region 1021, for example, the first carbon-based material exists in the region where the remaining region 1020 is adjacent to the first region 1021.

[0069] In the present application, the total pore area S1 of the outer region of the first carbon-based material is less than the total pore area S2 of the inner region. This means that the structure of the outer region of the first carbon-based material is denser than that of the inner region. In addition, the first carbon-based material in the present application satisfies "S2>S1", which means that the first carbon-based material has a pore structure that can be directly observed from a cross-sectional image (e.g., a scanning electron microscope image with a magnification of 1000 times). That is, the outer region has a smaller pore area in the main structure of the first carbon-based material.

[0070] refer to Figure 2 , which shows a schematic diagram of a cross-sectional image of a particle of the first carbon-based material 200 of the present application, and the cross-sectional image passes through the center of the particle of the first carbon-based material 200. Figure 2 As shown, D represents the volume distribution particle size Dv50 of the particles of the first carbon-based material 200, the area formed by a distance of 0.25D extending from the particle surface of the first carbon-based material 200 to the inside of the particle is recorded as the external area 201, and the area inside the external area 201 is recorded as the internal area 202.

[0071] The pore structure in the first carbon-based material can be observed by a cross-section polisher, for example, by testing the cross-sectional morphology (CP) of the negative electrode piece by ion polishing. Specifically, the negative electrode piece is cut into a sample to be tested of a certain size (for example, 2 cm×2 cm), and the negative electrode piece is fixed on the sample stage by paraffin; the sample stage is loaded into the sample holder and locked and fixed, the power of the argon ion cross-sectional polisher (for example, IB-09010 CP type argon ion cross-sectional polisher of JEOL Company of Japan) is turned on and vacuumed (for example, 10-4Pa), the argon gas flow rate (for example, 0.15MPa) and voltage (for example, 8KV) and polishing time (for example, 2h) are set, and the sample stage is adjusted to the swing mode to start polishing; a certain area in the first area 1021 is randomly selected in the sample to be tested for scanning test (for example, refer to JY / T010-1996, and use a scanning electron microscope for scanning), and the ion polishing cross-sectional morphology (CP) picture of the negative electrode piece is obtained at a certain magnification (for example, 1000 times). The internal structures of other negative electrode active materials (eg, additional carbon-based materials) in other regions 1020 can also be observed in this way, so that the first carbon-based material can be distinguished from the other negative electrode active materials. Figure 3 This is an ion polishing cross-section (CP) diagram of an embodiment of the first carbon-based material of the present application. It can be seen from the figure that the outer region of the second carbon-based material particle is denser than the inner region, satisfying S2>S1.

[0072] The pole piece design of the present application adopts a first carbon material with a specific structure in the upper layer. The carbon material particles have a pore structure, and the pore area of ​​the inner region is larger than the pore area of ​​the outer region, so it has better storage performance; the smaller pore area of ​​the outer region reflects the higher density near the surface of the material from the side, which effectively reduces the side reactions on the surface of the particles. At the same time, the pore structure with a larger area inside reserves a certain space, which can effectively alleviate the stress caused by the expansion of the material during the battery cycle, so that the battery has better cycle performance. In addition, when the material has a smaller particle size and is arranged in the first area of ​​the negative electrode film layer, the dynamic performance of the battery can be improved. Therefore, the secondary battery provided by the present application has further improved dynamic performance on the premise of having better storage performance and cycle performance.

[0073] According to some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is 7 μm-13 μm. Exemplarily, the volume distribution particle size Dv50 of the first carbon-based material is 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, etc. When the volume distribution particle size Dv50 of the first carbon-based material is within the above range, it is further beneficial to improve the kinetic performance of the secondary battery.

[0074] According to some embodiments, the first carbon-based material satisfies 1.5≤S2 / S1≤500, optionally, 2.5≤S2 / S1≤450. Exemplarily, the first carbon-based material satisfies 2.2≤S2 / S1≤400, 2.5≤S2 / S1≤300, 2.5≤S2 / S1≤250, 2.6≤S2 / S1≤200, 2.8≤S2 / S1≤150, or 3.0≤S2 / S1≤100. When S2 / S1 is within the above range, the storage performance and cycle performance of the battery can be further improved.

[0075] According to some embodiments, the area of ​​the pore structure in the outer region of the first carbon-based material is less than or equal to 0.15 μm 2 , can be selected to be less than or equal to 0.13μm 2 ; and / or, the inner region of the first carbon-based material includes one or more pores with an area greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of ​​0.15-2.0 μm 2 The pore structure of the outer region of the first carbon-based material includes the pore structure of the above size, which reflects that the outer region of the particles of the material is relatively dense and the pores of the pore structure are small. The electrolyte of the first carbon-based material with this structure is not easy to enter the interior of the particles, thereby reducing side reactions with the electrolyte. In addition, when the pore structure of the first carbon-based material has a specific pore area, on the one hand, sufficient and stable expansion space can be reserved for the volume change of the first carbon-based material particles, and on the other hand, the compaction density of the negative electrode film layer can be improved, thereby improving the storage performance, cycle performance and energy density of the secondary battery.

[0076] According to some embodiments, at least part of the surface of the first carbon-based material has a carbon coating. When at least part of the surface of the first carbon-based material has a carbon coating, it is conducive to the rapid migration of active ions, thereby further improving the kinetic performance of the secondary battery. Typically, the carbon coating can be an amorphous carbon coating. According to a specific embodiment, the entire surface of the first carbon-based material has a carbon coating.

[0077] The term "coating layer" or "carbon coating layer" mentioned herein has the same meaning as in the related field. It generally refers to a layer of carbon source material (such as asphalt) coated on the outer surface of the negative electrode active material, such as natural graphite particles, and formed into a carbon coating layer through heat treatment. The present application does not particularly limit the thickness of the carbon coating layer, and conventional coating thickness can be used in the embodiments.

[0078] According to some embodiments, the first carbon-based material includes primary particles. When the first carbon-based material exists mainly in the form of primary particles, it is conducive to the transmission of active ions, thereby improving the kinetic performance of the secondary battery. In some embodiments, the number of primary particles in the first carbon-based material accounts for ≥80%, optionally ≥85%, and further optionally ≥90%. In some specific embodiments, the first carbon-based material is all primary particles.

[0079] In some embodiments, the gram capacity of the first carbon-based material is ≥355 mAh / g, which can be 355 mAh / g-368 mAh / g. Exemplarily, the gram capacity of the first carbon-based material is 355 mAh / g, 360 mAh / g, 363 mAh / g, 365 mAh / g, 367 mAh / g, etc., or a value between any two values. A higher gram capacity is beneficial to the capacity density of the secondary battery.

[0080] In some embodiments, the graphitization degree of the first carbon-based material is ≥ 95.0%, and can be optionally 95.5%-98.0%. Exemplarily, the graphitization degree of the first carbon-based material is 95.0%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, etc., or a value between any two values. A higher graphitization degree is beneficial to the compaction of the powder, thereby facilitating the energy density of the secondary battery.

[0081] In some embodiments, the specific surface area of ​​the first carbon-based material is 1.0 m 2 / g-2.8m 2 / g, optional 1.3m 2 / g-2.1m 2 / g. Exemplarily, the specific surface area of ​​the first carbon-based material is 1.1m 2 / g, 1.3m 2 / g, 1.5m 2 / g, 1.7m 2 / g, 1.9m 2 / g, 2.1m 2 / g, 2.4m 2 / g, etc., or a value between any two values. A larger specific surface area is further beneficial to improving the kinetic performance of the secondary battery.

[0082] According to some embodiments, when the first carbon-based material satisfies at least one of the following items, it is beneficial to at least one of the kinetic performance, energy density and cycle performance of the secondary battery.

[0083] (1) The first carbon-based material satisfies: (Dv90-Dv10) / Dv50≤1.40, which can be 0.90-1.40.

[0084] (2) The powder compaction density of the first carbon-based material under a pressure of 50,000 N is 1.75 g / cm 3 -2.0g / cm 3 , optional 1.82g / cm 3 -1.98g / cm 3 .

[0085] (3) The tap density of the first carbon-based material is 0.90-1.30 g / cm 3 , optionally 0.95-1.25g / cm 3 .

[0086] (4) The volume distribution particle size Dv90 of the first carbon-based material is 13.0 μm-30.0 μm, optionally 16.0 μm-23.0 μm.

[0087] According to some embodiments, the area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the second region of the negative electrode film layer, the second region is arranged between the negative electrode collector and the first region, the second region includes a second negative electrode active material, and the second negative electrode active material includes a second carbon-based material.

[0088] In the embodiment, the second region of the negative electrode film layer is close to the negative electrode current collector (when the negative electrode current collector is used as the base layer, it is also called the lower layer of the negative electrode film layer). The second carbon-based material different from the first carbon-based material is arranged in this region, which will not significantly affect the dynamic performance of the secondary battery, and can also improve other secondary properties, such as energy density, etc., by virtue of the characteristics of the second carbon-based material.

[0089] In some specific embodiments, the second carbon-based material includes artificial graphite. Artificial graphite has insufficient dynamic performance compared to other carbon-based materials, such as soft carbon, hard carbon, and natural graphite. When artificial graphite is arranged in the second area, it will not have a significant impact on the dynamic performance of the secondary battery, and at the same time, since artificial graphite has a good powder compaction density, it can improve the energy density of the secondary battery.

[0090] In the described embodiment, the aforementioned first carbon-based material is mainly arranged in the first area of ​​the negative electrode film layer, and the second carbon-based material including artificial graphite is mainly arranged in the second area of ​​the negative electrode film layer. The combination of the two can enable the secondary battery to improve the dynamic performance while taking into account the energy density and cycle performance.

[0091] More specifically, the first carbon-based material in the first region has good kinetic properties, which can improve the charging speed, especially the speed in the early stage of charging (such as the first 50% of the capacity at the beginning of charging) can be significantly improved. In addition, because the two different carbon-based materials have different densities after cold pressing under the same pressure, different densities are formed in the negative electrode film layer. The density of the upper layer, which is mainly the first carbon-based material, is smaller than the density of the lower layer, which is mainly artificial graphite. It can provide more migration channels for active ions, which is beneficial for the active ions to migrate to the lower layer of the negative electrode film layer and further contact with the second carbon-based material, which is also beneficial to improve the speed in the later stage of charging (such as the last 50% of the capacity after starting charging).

[0092] Compared with the method of reducing the compaction density of the negative electrode film layer to improve the kinetic performance of the negative electrode, or increasing the compaction density of the negative electrode film layer to improve the energy density, the implementation method can improve the kinetic performance of the secondary battery while taking into account the energy density.

[0093] In addition, since artificial graphite has a stable structure, it is beneficial to the cycle life of the secondary battery.

[0094] See also Figures 4 to 6 , which shows schematic diagrams of three different embodiments of a negative electrode sheet having a first region and a second region, wherein different negative electrode active materials are present in the two regions. Figures 4 to 6 As shown, Figure 1 Similar to the figure, the negative electrode sheet 10 includes a negative electrode current collector 101 and a negative electrode film layer 102 formed on at least one surface of the negative electrode current collector 101. The negative electrode film layer 102 has a first surface 102a away from the negative electrode current collector 101 and a second surface 102b arranged opposite to the first surface 102a. The thickness of the negative electrode film layer 102 is H. On the side away from the negative electrode current collector 101, the area within the thickness range from the second surface 102b of the negative electrode film layer to 0.3H is the first area 1021 of the negative electrode film layer. On the side close to the negative electrode current collector 101, the area within the thickness range from the first surface 102a of the negative electrode film layer to 0.3H is recorded as the second area 1022 of the negative electrode film layer. The first area 1021 includes a first negative electrode active material, which includes the aforementioned first carbon-based material. The second area 1022 includes a second negative electrode active material, and the second negative electrode active material includes a second carbon-based material different from the aforementioned first carbon-based material. Between the first region 1021 and the second region 1022, the region occupying a thickness range of 0.4H is recorded as the middle region 1023. It is easy to understand that according to Figures 4 to 7 , the middle region 1023 includes at least one of the first carbon-based material and the second carbon-based material.

[0095] Specifically, the figure shows that the second carbon-based material and the first carbon-based material are sequentially coated on the negative electrode current collector 101 . Figure 4 It is shown that the thickness of the two layers each occupies about one half of the thickness of the negative electrode film layer 102 . Figure 5 It is shown that the thickness of the second carbon-based material occupies about 70% of the thickness of the negative electrode film layer 102 , while the thickness of the first carbon-based material occupies about 30% of the thickness of the negative electrode film layer 102 . Figure 6 Shown with Figure 5 In the opposite configuration, the thickness of the first carbon-based material occupies about 70% of the thickness of the negative electrode film layer 102 , while the thickness of the second carbon-based material occupies about 30% of the thickness of the negative electrode film layer 102 .

[0096] It should be understood that Figures 4 to 6 The diagram in FIG. 1 is a schematic diagram of an ideal situation. The present application has no particular restrictions on the ratio of the thickness of the first carbon-based material to the second carbon-based material, for example, the two can be in the range of 3:7-7:3. Exemplarily, the ratio of the thickness of the first carbon-based material to the second carbon-based material is 4:6, 5:5, 6:4, etc., or a ratio between any two ratios.

[0097] It should also be understood that Figures 4 to 6 The middle region 1023 in the figure shows a clear boundary with the other two regions, but in fact there is no such obvious interface. As mentioned above, the first carbon-based material and the second carbon-based material may exist simultaneously within the middle region 1023. Similarly, there is no obvious interface between the coating containing the first carbon-based material and the coating containing the second carbon-based material.

[0098] According to some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is smaller than the volume distribution particle size Dv50 of the second carbon-based material. Specifically, the volume distribution particle size Dv50 of the second carbon-based material is 13μm-19μm, and can be further optionally 14μm-18μm. The volume distribution particle size Dv50 of the second carbon-based material is 14μm, 15μm, 16μm, 17μm, 18μm, etc., or a value between any two values. When the second carbon-based material has a larger particle size relative to the first carbon-based material, its adverse effect on the kinetic performance of the secondary battery can be minimized.

[0099] According to some embodiments, the second carbon-based material, especially the artificial graphite, has a powder compaction density of 1.80 g / cm under a pressure of 50,000 N. 3 -2.05g / cm 3 , optional 1.85g / cm 3 -2.03g / cm 3 For example, the powder compaction density of the second carbon-based material under a pressure of 50000N is 1.80 g / cm3 , 1.85g / cm 3 , 1.90g / cm 3 , 1.95g / cm 3 , 2.00g / cm 3 , 2.05g / cm 3 , or a value between any two values ​​of the composition range. The second carbon-based material with high powder compression density is beneficial to improving the energy density of the secondary battery when arranged in the lower layer of the negative electrode film layer.

[0100] According to some embodiments, the second carbon-based material includes artificial graphite of secondary particles. Optionally, the number of artificial graphite of the secondary particles in the second carbon-based material accounts for greater than or equal to 80%. When the second carbon-based material includes artificial graphite of secondary particles, in cold pressing, each primary particle in the secondary particles is not easy to change the crystal plane orientation due to pressure. Therefore, compared to using it only in the form of primary particles, the use of secondary particles can effectively reduce the situation where the crystal plane orientation of artificial graphite in cold pressing tends to be parallel to the negative electrode current collector, which is beneficial to shorten the embedding and extraction of active particles, thereby further facilitating the kinetic performance of the secondary battery, especially improving the charging speed in the latter stage of charging. In some specific embodiments, when the second carbon-based material is mainly in the form of secondary particles, or all in the form of secondary particles, the kinetic performance of the secondary battery can be improved.

[0101] According to some embodiments, the particle size distribution of the second carbon-based material satisfies (Dv90-Dv10) / Dv50≤1.25, which can be optionally 0.90-1.25. Exemplarily, the particle size distribution of the second carbon-based material satisfies (Dv90-Dv10) / Dv50 is 0.9, 1, 1.1, 1.2, etc., or a value between the ranges consisting of any two values. When the particle size distribution of the second carbon-based material is narrow, the number of particles with larger particle sizes is reduced, which is more conducive to contact with active ions, thereby improving the energy density of the secondary battery while better taking into account the kinetic performance.

[0102] According to some embodiments, the gram capacity of the first carbon-based material is greater than the gram capacity of the second carbon-based material. In some embodiments, the gram capacity of the second carbon-based material is 350mAh / g-365mAh / g, optionally 352mAh / g-362mAh / g. Exemplarily, the gram capacity of the second carbon-based material is 352mAh / g, 355mAh / g, 358mAh / g, 360mAh / g, 362mAh / g, etc., or a value between the ranges consisting of any two values. The higher gram capacity of the first carbon-based material and the second carbon-based material can jointly improve the energy density of the secondary battery.

[0103] According to some embodiments, the degree of graphitization of the first carbon-based material is greater than the degree of graphitization of the second carbon-based material. In some embodiments, the degree of graphitization of the second carbon-based material is 90.0%-95.5%, optionally 92%-95.5%. Exemplarily, the degree of graphitization of the second carbon-based material is 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, etc., or a value between the ranges consisting of any two values. A higher degree of graphitization is beneficial to powder compaction, which is beneficial to the energy density of the secondary battery.

[0104] According to some embodiments, the specific surface area of ​​the first carbon-based material is greater than the specific surface area of ​​the second carbon-based material. In some embodiments, the specific surface area of ​​the second carbon-based material is 0.8 m 2 / g-2m 2 / g, optional 1.1m 2 / g-1.7m 2 / g. Exemplarily, the specific surface area of ​​the second carbon-based material is 1.0 m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, etc., or a value between any two values. Controlling the second carbon-based material to have a smaller specific surface area is beneficial to reducing side reactions and further beneficial to improving the cycle performance of the secondary battery.

[0105] According to some embodiments, the second carbon-based material can further contribute to the energy density of the secondary battery when satisfying at least one of the following items.

[0106] (1) The tap density of the second carbon-based material is 0.85-1.25 g / cm 3 , optional: 0.90-1.15g / cm 3 ;

[0107] (2) The second carbon-based material satisfies 0.050≤I D / I G ≤0.300, optionally, 0.070≤I D / I G ≤0.200, I D Indicates that the Raman spectrum is at 1350±50cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±50cm -1The G peak intensity at .

[0108] According to some embodiments, the negative electrode film layer also includes a silicon-based material, and optionally, the mass proportion of the silicon-based material in the negative electrode film layer is less than or equal to 10%, and can be optionally 5%-10%. Silicon-based materials have higher lithium insertion potentials, which are beneficial to improving the kinetic performance of secondary batteries. At the same time, silicon-based materials have high gram capacity, which is beneficial to improving the energy density of secondary batteries. However, the lithium insertion expansion of silicon-based materials is large and the stability is low, which is not conducive to the cycle performance, so the amount added cannot be too much. Exemplarily, the mass proportion of the silicon-based material in the negative electrode film layer is 3%, 5%, 6%, 8%, etc., or a value between any two values. The silicon-based material can be mixed with the first carbon-based material as the first negative electrode active material, and / or the silicon-based material can be mixed with the second carbon-based material as the second negative electrode active material.

[0109] The present application has no particular restrictions on silicon-based materials, and silicon-based materials conventionally used as negative electrode active materials in the art can be used. Exemplarily, the silicon-based material can be selected from at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys.

[0110] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0111] In some embodiments, the negative electrode active material may further adopt a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may also include at least one of the following materials: natural graphite, soft carbon, hard carbon, tin-based materials, and lithium titanate. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0112] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0113] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0114] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0115] The present application does not particularly limit the content of the binder and / or other auxiliary agents, if any, in the negative electrode film layer. A person skilled in the art can determine the appropriate content of the binder and / or other auxiliary agents through routine tests in the relevant field.

[0116] According to some embodiments, the negative electrode film layer satisfies at least one of the following items, which is beneficial to at least one of the kinetic performance, energy density, and cycle performance of the secondary battery.

[0117] (1) The compaction density of the negative electrode film layer is ≤1.85 g / cm 3 , optionally 1.7-1.85 g / cm 3 The compaction density within this range is beneficial to the energy density of the secondary battery. For example, the compaction density of the negative electrode film layer is 1.7 g / cm 3 , 1.75g / cm 3 , 1.8g / cm 3 , 1.85g / cm 3 etc., or any value between any two values.

[0118] (2) The porosity of the negative electrode film layer is 18.0%-38.0%, and optionally 19.0%-34.0%. For example, the porosity of the negative electrode film layer is 19%, 21%, 23%, 25%, 27%, 29%, 31%, 33%, etc., or a value between any two values. The porosity within this range is beneficial to the migration of active ions, thereby being beneficial to the kinetic performance of the secondary battery.

[0119] (3) The OI value of the negative electrode film layer is ≤30.0, and can be optionally 8.0-23.0. For example, the OI value of the negative electrode film layer is 8, 10, 12, 14, 16, 18, 20, 22, etc., or a value between any two values. The OI value within this range reflects that the crystal plane orientation of the carbon-based material in the negative electrode film layer is not completely parallel to the negative electrode current collector, which is beneficial to shortening the migration path of the active ions and is beneficial to the kinetic performance of the secondary battery.

[0120] (4) The thickness of the negative electrode film layer is greater than or equal to 40 μm, and optionally 40-140 μm. For example, the thickness of the negative electrode film layer is 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, etc., or a value between any two values, but not limited thereto.

[0121] The above embodiments are described only by taking the composition of the negative electrode film layer on the surface of one side of the negative electrode current collector as an example. It should be understood that the negative electrode film layer described in the above embodiments can be arranged on any one or both of the two surfaces opposite to each other in the thickness direction of the negative electrode current collector. It should be noted that the parameters of the negative electrode film layer (such as compaction density, surface density, porosity, thickness, etc.) given in this application refer to the parameters of the negative electrode film layer on one side of the negative electrode current collector. When the negative electrode film layer is arranged on both sides of the negative electrode current collector, the parameters of the negative electrode film layer on either side meet the requirements of this application, which is considered to fall within the protection scope of this application.

[0122] In the present application, the negative electrode plate does not exclude that other additional functional layers may be included in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode plate also includes a protective layer covering the surface of the negative electrode film layer.

[0123] In the present application, the pore area, S1, and S2 values ​​of the first carbon-based material can be obtained by using a cross-section polisher (such as the IB-09010 CP argon ion cross-section polisher produced by Japan's JEOL company) to obtain the cross-section of the first carbon-based material; then, referring to JY / T010-1996, a scanning electron microscope (such as the Sigma300 scanning electron microscope produced by Germany's ZEISS company) is used to scan the cross-section of the first carbon-based material; finally, the pore area of ​​any one hole in the first carbon-based material is obtained by image processing software (such as AVIZO); as well as the total pore area S1 of the external region and the total pore area S2 of the internal region, and thereby the value of S2 / S1 is obtained. Exemplarily, samples can be obtained from different regions of the negative electrode sheet in the secondary battery, and at least 5 positions (such as 5, 10, 15 or even more) are randomly selected from the sample to obtain cross sections using a cross-section polisher, and at least 10 particles (such as 10, 20, 50 or even more particles) are randomly selected from the scanning electron microscope images of each cross section. The total pore area S2' and the total pore area S1' of the inner region of each particle cross section are obtained by image processing software according to the above definition, and the S2' / S1' value of each particle cross section is obtained. The arithmetic mean of S2' / S1' of all the measured particle cross sections is calculated as the S2 / S1 value of the first carbon-based material.

[0124] In the X-ray diffraction (XRD) analysis test of the present application, a copper target can be used as an anode target, and CuKα rays can be used as a radiation source, with a ray wavelength of The scanning 2θ angle range was 20°-80°, and the scanning rate was 4° / min.

[0125] In this application, the volume distribution particle sizes Dv10, Dv50, and Dv90 of materials (such as the first carbon-based material, the second carbon-based material, etc.) are well-known in the art, which respectively represent the particle sizes corresponding to the cumulative volume distribution percentages of the materials reaching 10%, 50%, and 90%, and can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer with reference to GB / T19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0126] In the present application, whether there is a coating layer on the surface of a material (eg, the first carbon-based material, the second carbon-based material, etc.) can be determined by transmission electron microscopy.

[0127] In the present application, the specific surface area BET of a material (e.g., a first carbon-based material, a second carbon-based material, etc.) is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be tested by nitrogen adsorption specific surface area analysis test method with reference to GB / T 19587-2017, and calculated by BET (Brunauer Emmett Teller) method. The test instrument can be the Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.

[0128] In the present application, the graphitization degree of a material (e.g., the first carbon-based material, the second carbon-based material) is a well-known meaning in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (e.g., Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d of the C(002) crystal plane in the material crystal structure. 002 Then according to the formula g = (0.344-d 002 ) / (0.344-0.3354)×100% to calculate the graphitization degree. In the above formula, d 002 It is the average interlayer spacing of the C(002) crystal plane in the material's crystal structure expressed in nanometers (nm).

[0129] In the present application, the gram capacity of materials (such as the first carbon-based material, the second carbon-based material, etc.) has a well-known meaning in the art and can be tested by methods known in the art. An exemplary test method is as follows: the sample powder is mixed evenly with the conductive agent carbon black (Super P), the binder polyvinylidene fluoride (PVDF) and the solvent N-methylpyrrolidone (NMP) in a mass ratio of 91.6:1.8:6.6 to form a slurry; the prepared slurry is applied on the surface of the negative electrode current collector copper foil, and dried in an oven for use; ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare a concentration of 1 mol / L The electrolyte was then used as a counter electrode and a polyethylene (PE) film as an isolation membrane, and the above electrolyte was assembled into a CR2430 button cell in an argon-protected glove box; the button cell was left to stand for 12 hours, and then discharged at 0.05C constant current to 0.005V at 25°C, left to stand for 10 minutes, and then discharged at 50μA constant current to 0.005V, left to stand for 10 minutes, and then discharged at 10μA constant current to 0.005V; then charged at 0.1C constant current to 2V, and the charge capacity was recorded. The ratio of the charge capacity to the sample mass is the gram capacity of the corresponding material (e.g., the first carbon-based material, the second carbon-based material, etc.).

[0130] In the present application, the powder compaction density of a material (e.g., the first carbon-based material, the second carbon-based material, etc.) is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured by an electronic pressure testing machine (e.g., a UTM7305 electronic pressure testing machine) with reference to GB / T 24533-2009. An exemplary test method is as follows: Weigh 1 g of sample powder and add a bottom area of ​​1.327 cm 2 In the mold, the pressure is increased to 50000N, the pressure is maintained for 30s, and then the pressure is released and maintained for 10s. Then the powder compaction density of the material under the pressure of 50000N is recorded and calculated.

[0131] In the present application, the tap density of a material (e.g., a first carbon-based material, a second carbon-based material, etc.) is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, GB / T 5162-2006 can be referred to and a powder tap density tester can be used for measurement. The test instrument can be Dandong Baite BT-301, and the test parameters are as follows: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, vibration number 5000 times, and measuring cylinder 25mL.

[0132] In the present application, primary particles and secondary particles have the meanings known in the art. Primary particles refer to non-agglomerated particles. Secondary particles refer to agglomerated particles formed by aggregation of primary particles. Primary particles and secondary particles can be distinguished by using a scanning electron microscope (SEM) image.

[0133] In the present application, the number ratio of primary particles in the first carbon-based material and / or the second carbon-based material refers to: for example, randomly select a test sample in the negative electrode film layer, randomly select multiple test areas in the test sample, use a scanning electron microscope to obtain images of the multiple test areas, and count the number of first carbon-based materials with primary particle morphology in each image to the total number of first carbon-based material particles. The average value of multiple statistical results is the number ratio of primary particles in the first carbon-based material.

[0134] In the present application, the number ratio of secondary particles in the first carbon-based material and / or the second carbon-based material refers to: for example, randomly select a test sample in the negative electrode film layer, randomly select multiple test areas in the test sample, use a scanning electron microscope to obtain images of the multiple test areas, and count the number of second carbon-based materials with secondary particle morphology in each image to the total number of second carbon-based material particles. The average value of multiple statistical results is the number ratio of secondary particles in the second carbon-based material.

[0135] In this application, the surface density of the negative electrode film layer has a well-known meaning in the art and can be tested by methods known in the art. For example, a negative electrode sheet coated on one side and cold pressed can be taken (if it is a negative electrode sheet coated on both sides, the negative electrode film layer on one side can be wiped off first), punched into small discs with an area of ​​S', weighed, and recorded as M1. Then wipe off the negative electrode film layer of the weighed negative electrode sheet, weigh the weight of the negative electrode collector, and record it as M0. Surface density of negative electrode sheet = (M1-M0) / S'.

[0136] In the present application, the compaction density of the negative electrode film layer is a well-known meaning in the art and can be tested by methods known in the art. [Compaction density of the negative electrode film layer = surface density of the negative electrode film layer / thickness of the negative electrode film layer].

[0137] In the present application, the porosity of the negative electrode film layer has a well-known meaning in the art and can be measured by methods known in the art. An exemplary test method is as follows: take a negative electrode sheet that has been coated on one side and cold pressed (if it is a negative electrode sheet coated on both sides, the negative electrode film layer on one side can be wiped off first), punch it into small disc samples of a certain area, and calculate the apparent volume V1 of the negative electrode sheet; refer to GB / T24586-2009, use an inert gas (such as helium or nitrogen) as a medium, adopt a gas replacement method, and use a true density tester to measure the true volume V2 of the negative electrode sheet. The porosity of the negative electrode film layer = (V1-V2) / V1×100%. Multiple negative electrode sheet samples (such as 30 pieces) with good appearance and no powder falling on the edges can be taken for testing, and the results are averaged, thereby improving the accuracy of the test results. The test instrument can be a Micromeritics AccuPyc II 1340 true density tester.

[0138] In the present application, the OI value of the negative electrode film layer has a well-known meaning in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain an X-ray diffraction pattern of the negative electrode sheet. According to OI value = I 004 / I 110 The OI value of the negative electrode film layer is calculated. 004 is the integrated area of ​​the diffraction peak of the 004 crystal plane of crystalline carbon in the negative electrode film layer, I 110 is the integrated area of ​​the diffraction peak of the 110 crystal plane of the crystalline carbon in the negative electrode film layer. In the X-ray diffraction analysis test of the present application, a copper target can be used as the anode target, and CuKα rays can be used as the radiation source. The ray wavelength is The scanning 2θ angle range was 20°-80°, and the scanning rate was 4° / min.

[0139] The thickness of the negative electrode film layer is well known in the art and can be tested by methods known in the art, such as using a micrometer (e.g., Mitutoyo 293-100, with an accuracy of 0.1 μm). The thickness range given in this application is the thickness range of the negative electrode film layer on one side of the negative electrode current collector. If the thickness of the negative electrode film layer on either side of the negative electrode current collector is within the range given in this application, it satisfies this application.

[0140] It should be noted that the above-mentioned various parameter tests on the negative electrode active material or the negative electrode film layer can be conducted by sampling and testing from the prepared secondary battery according to the following steps.

[0141] Discharge the secondary battery (for safety reasons, the secondary battery is generally fully discharged); disassemble the secondary battery and take out the negative electrode sheet, and soak the negative electrode sheet in dimethyl carbonate for a certain period of time (e.g., 2h-10h); then take out the negative electrode sheet and dry it at a certain temperature and time (e.g., 60°C, more than 4h), and take out the negative electrode sheet after drying. At this time, the above-mentioned parameters related to the negative electrode film layer can be sampled from the dried negative electrode sheet, such as the surface density, compaction density, porosity, thickness, etc. of the negative electrode film layer.

[0142] The dried negative electrode sheet is baked at a certain temperature and time (for example, 400°C for more than 2h), and a region of the baked negative electrode sheet is selected to sample the negative electrode active material (a blade can be used to scrape the powder for sampling); the collected negative electrode active material is sieved (for example, sieved with a 200-mesh sieve), and finally a sample that can be used to test the parameters of the above-mentioned negative electrode active materials is obtained.

[0143] In the present application, the above-mentioned first carbon-based material can be prepared by the following method of the present application; the above-mentioned second carbon-based material can be obtained by commercial purchase, or can also be prepared by the following method of the present application.

[0144] In some embodiments, the preparation method of the first carbon-based material includes: step 1, providing a raw material having a plurality of pore structures; step 2, mixing the raw material and the filling material uniformly in a predetermined proportion, then keeping the mixture at a first temperature T1 for a first time t1, and cooling to room temperature to obtain an intermediate; step 3, keeping the obtained intermediate at a second temperature T2 for a second time t2, and obtaining the first carbon-based material after the mixture is finished.

[0145] In some embodiments, in step 1, the raw material for preparing the first carbon-based material includes natural graphite. Optionally, the natural graphite includes one or more of flake graphite, natural spherical graphite and microcrystalline graphite, especially natural spherical graphite.

[0146] "Natural spherical graphite" refers to natural graphite with a spherical or quasi-spherical shape, and not all natural graphite particles are controlled to be ideal spheres. In some embodiments, natural spherical graphite with a desired particle size and morphology can be obtained by pre-treating flake graphite, and optionally, the pre-treatment includes crushing, classification, spheroidization, purification and other processes.

[0147] In some embodiments, in step 1, the volume distribution particle size Dv50 of the raw material may be 6 μm to 13 μm.

[0148] In some embodiments, in step 1, the specific surface area of ​​the raw material may be ≥ 2.5 m 2 / g, optional 2.5m 2 / g~10.0m 2 When the specific surface area of ​​the raw material is within the above range, it is beneficial to carry out subsequent filling treatment and obtain the first carbon-based material with the required specific surface area, and it is also beneficial for the first carbon-based material to have both high capacity and high first coulombic efficiency. In addition, it is also beneficial for the first carbon-based material to have better kinetic properties.

[0149] In some embodiments, in step 2, the softening point temperature of the filling material is 90° C. to 150° C. Optionally, the softening point temperature of the filling material is 94° C. to 146° C., 94° C. to 142° C., 94° C. to 138° C., 94° C. to 134° C., 94° C. to 130° C., 104° C. to 146° C., 104° C. to 142° C., 104° C. to 138° C., 104° C. to 134° C., 104° C. to 130° C.

[0150] In some embodiments, in step 2, the volume distribution particle size Dv50 of the filler material is less than or equal to 6 μm, and can be selected from 1 μm to 6 μm, 1 μm to 5 μm, 2 μm to 5 μm, and 3 μm to 5 μm. This is conducive to the filler material being melted by heat and filling into the pore structure of the raw material, and is also conducive to improving the dispersion uniformity of the filler material and the raw material.

[0151] In some embodiments, in step 2, the coking value of the filler material is 15% to 40%, and can be optionally 18% to 34%. In the present application, the coking value of the filler material has a meaning known in the art, and can be measured using instruments and methods known in the art. For example, it can be measured with reference to GB / T 8727-2008.

[0152] In some embodiments, in step 2, the filling material includes one or more of coal tar, petroleum asphalt, polymer compounds and resins, and may optionally include one or more of coal tar and petroleum asphalt.

[0153] In some embodiments, in step 2, the mass ratio of the above-mentioned filling material to the above-mentioned raw material is (10-40):100, and can be optionally (10-30):100, (10-25):100, (10-20):100, (12-30):100, (14-28):100, (15-25):100.

[0154] In step 2, by adjusting one or more parameters such as the type, softening point, coking value, and addition amount of the filling material within the above-mentioned range, it is helpful to adjust the number and / or pore size of pores in the outer and inner regions of the first carbon-based material within a suitable range, which is helpful to adjust the S2 / S1 of the first carbon-based material within a suitable range.

[0155] By adjusting the type, softening point, coking value, addition amount and other parameters of the filling material within the above range, the viscosity of the filling material is not high after it is heated and melted, and it maintains good fluidity. At the same time, it is not easy to adhere to the raw material particles, which can reduce the agglomeration of the raw material particles in the subsequent preparation process. This can also reduce the problems of increased surface defects of the first carbon-based material particles and increased surface active sites due to the need to add a depolymerization step.

[0156] In some embodiments, in step 2, the heating process of uniformly mixing the raw material and the filling material in a predetermined ratio and then heating the mixture to the first temperature T1 may be a staged heating process.

[0157] In some embodiments, the phased temperature increasing process includes a first temperature increasing process, a second temperature increasing process, and a third temperature increasing process.

[0158] In some embodiments, the first temperature rising process is to raise the temperature to 200° C. to 250° C. and keep the temperature at this temperature for 0.5 h to 3 h.

[0159] In some embodiments, the second temperature increase process is to increase the temperature to 450°C to 550°C and keep the temperature at this temperature for 0h to 2h. When the holding time is 0h, it means that when the temperature is increased to the range of 450°C to 550°C, no holding treatment is performed, but the temperature continues to be increased to the first temperature T1.

[0160] In some embodiments, the third temperature increasing process is to increase the temperature to the first temperature T1 and keep the temperature at the first time t1.

[0161] In the staged heating process, the temperature is first raised to 200°C ~ 250°C. Since the heating temperature is higher than the softening point of the filling material, the filling material is melted and softened by the heat. Keeping it warm for 0.5h ~ 3h allows it to flow and fill into the pore structure of the raw material; then the temperature is raised to 450°C ~ 550°C. At this time, the melted and softened filling material undergoes a carbonization reaction, gradually forming a semi-coke state and turning into a viscous liquid or solid, thereby preventing the filling material from entering the entire pore structure of the raw material; finally, the temperature is raised to the first temperature. At this time, the filling material undergoes a carbonization reaction, thereby enabling the pore structure occupied by the filling material to be effectively filled.

[0162] In some embodiments, in step 2, the temperature is raised to the first temperature T1 at a rate of 1°C / min to 10°C / min. For example, the heating rate may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any range thereof. Optionally, the heating rate is 1.5°C / min to 8°C / min, 1.5°C / min to 6°C / min, 2°C / min to 6°C / min, 2°C / min to 5°C / min.

[0163] In some embodiments, the heating rate of the first heating process may be 1°C / min to 10°C / min, and may be 1.5°C / min to 8°C / min, 1.5°C / min to 6°C / min, 2°C / min to 6°C / min, or 2°C / min to 5°C / min. In some embodiments, the heating rate of the second heating process may be 1°C / min to 10°C / min, and may be 2°C / min to 8°C / min. In some embodiments, the heating rate of the third heating process may be 1°C / min to 10°C / min, and may be 2°C / min to 8°C / min.

[0164] In some embodiments, in step 2, the first temperature T1 is 800°C to 1200°C. For example, the first temperature T1 may be 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1200°C or any range thereof. Optionally, the first temperature T1 is 800°C to 1100°C, 850°C to 1100°C, 900°C to 1100°C, 850°C to 1000°C.

[0165] In some embodiments, in step 2, the first time t1 is 1 hour to 5 hours. For example, the first time t1 can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours or any range thereof. Optionally, the first time t1 is 2 hours to 4 hours.

[0166] In some embodiments, in step 2, the heat treatment can be carried out in a medium frequency furnace, a roller kiln, a rotary kiln, a push plate kiln, a vertical granulation kettle, a horizontal granulation kettle, a vertical reactor, a horizontal reactor or a drum furnace, etc., which can perform programmed temperature increase.

[0167] In some embodiments, in step 2, the heat treatment atmosphere may be a protective gas atmosphere. The protective gas may include one or more of nitrogen, argon, and helium.

[0168] In step 2, by adjusting one or more of the heating rate, the first temperature, the first time, the heating process, etc. within the above-mentioned range, it is helpful to adjust the number of pores and / or the pore size in the outer region and the inner region of the first carbon-based material within a suitable range, and then it is helpful to adjust the S2 / S1 of the first carbon-based material within a suitable range.

[0169] In some embodiments, in step 3, the first temperature T2 is 1600° C. to 2800° C. Optionally, the second temperature T2 is 1600° C. to 2700° C., 1600° C. to 2600° C., 1600° C. to 2500° C., 1600° C. to 2400° C., 1800° C. to 2600° C., 1800° C. to 2500° C., 1800° C. to 2400° C., 2000° C. to 2500° C., 2000° C. to 2400° C.

[0170] In some embodiments, in step 3, the second time t2 is 1.5 hours to 6 hours. For example, the second time t1 can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours or any range thereof. Optionally, the second time t2 is 2 hours to 5 hours.

[0171] In some embodiments, in step 3, the heat treatment may be performed in a medium frequency furnace, a box-type graphitization furnace, an Acheson graphitization furnace, a continuous graphitization furnace, or an inner-string graphitization furnace.

[0172] In some embodiments, in step 3, the medium frequency furnace and the continuous graphitization heat treatment atmosphere may be a protective gas atmosphere. The protective gas may include one or more of nitrogen, argon, and helium.

[0173] In step 3, by adjusting one or more of the second temperature and the second time within the above range, it is beneficial to adjust the content of disordered carbon in the first carbon-based material within a suitable range, which is beneficial for the first carbon-based material to have a suitable graphitization degree, interlayer spacing and I D / I G wait.

[0174] In the preparation method of the above-mentioned first carbon-based material, by adjusting one or more of the parameters of natural graphite, the parameters of the filling material, the heating rate, the first temperature, the first time, the heating process, the second temperature, the second time, etc. within the above-mentioned range, it is beneficial to adjust the S2 / S1, graphitization degree, gram capacity, specific surface area, particle size, powder compaction density, tap density and other parameters of the second carbon-based material.

[0175] According to some embodiments, the first carbon-based material may have a coating layer. The preparation method further includes step 4: mixing the first carbon-based material prepared above with an organic carbon source, and carbonizing it at a third temperature T3. The organic carbon source may be a carbon-containing material suitable for coating known in the art, for example, it may include one or more of coal tar, petroleum asphalt, phenolic resin, coconut shell, etc. In some embodiments, the first carbon-based material mixed with the organic carbon source is kept at a third temperature T3 of 1150 to 1500°C for 1-3 hours for carbonization, thereby obtaining a first carbon-based material having a carbon coating layer on at least part of its surface.

[0176] In some embodiments, artificial graphite as the second carbon-based material can be prepared according to methods in the prior art. For example, it can be prepared by the following method.

[0177] Providing raw materials; crushing and shaping the raw materials to obtain a first intermediate; graphitizing the first intermediate to obtain a second intermediate; mixing the second intermediate with an organic carbon source and then carbonizing it; and finally screening to obtain a second carbon-based material.

[0178] The raw material can be one or more of petroleum coke, needle coke, pitch coke and metallurgical coke. The raw material can be crushed by a mechanical mill or a roller mill, and shaped by a shaping machine.

[0179] In some embodiments, the graphitization temperature is 2800° C.-3200° C. By adjusting the graphitization temperature and / or the graphitization time, it is beneficial for the second carbon-based material to have a suitable graphitization degree.

[0180] In some embodiments, the organic carbon source may be a carbon-containing material suitable for coating known in the art, for example, it may include one or more of coal tar, petroleum tar, phenolic resin, coconut shell, etc. By adjusting the amount of the organic carbon source added, it is beneficial to adjust the parameters such as the specific surface area, graphitization degree, and gram capacity of the second carbon-based material. The carbonization temperature may be 900°C-1300°C. By adjusting the carbonization temperature and / or the carbonization holding time, it is beneficial to adjust the parameters such as the specific surface area, graphitization degree, and gram capacity of the second carbon-based material.

[0181] During the preparation process, by adjusting one or more parameters of the equipment (such as mechanical mill or roller mill, shaping machine, granulator, etc.), the parameters of the raw materials, the amount of organic carbon source added, the amount of binder added, the graphitization temperature, the graphitization time, etc., it is beneficial to adjust the graphitization degree, powder compaction density, gram capacity, particle size, specific surface area and other parameters of the second carbon-based material.

[0182] In order to obtain artificial graphite of secondary particles, the precursor can be granulated with a binder asphalt before graphitization, and then the granulated product is graphitized at 2800° C.-3200° C. to obtain artificial graphite of secondary particles.

[0183] The present application also provides a method for preparing the negative electrode sheet of the present application. The method comprises the following steps: providing a first negative electrode slurry containing the first negative electrode active material in each of the above embodiments and a second negative electrode slurry containing the second negative electrode active material in each of the above embodiments; coating the second negative electrode slurry on the negative electrode current collector, coating the first negative electrode slurry on the second negative electrode slurry, and obtaining the negative electrode sheet after drying and cold pressing.

[0184] In some embodiments, the first negative electrode slurry and the second negative electrode slurry may further optionally include the above-mentioned conductive agent, binder, other optional auxiliary agents and solvent (eg, deionized water), respectively.

[0185] The first slurry and the second slurry can be applied at the same time or in two times. In some embodiments, the first slurry and the second slurry are applied at the same time. Applying at the same time can reduce the negative electrode film resistance, thereby further improving the dynamic performance and cycle performance of the secondary battery.

[0186] The coating weight of the first slurry and the second slurry can be adjusted according to actual conditions.

[0187] [Positive electrode]

[0188] The secondary battery of the present application further comprises a positive electrode sheet. The positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer comprises a positive electrode active material. The present application has no particular restrictions on the positive electrode sheet.

[0189] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0190] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0191] In some embodiments, when the battery cell is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0192] The battery will be accompanied by the deintercalation and consumption of active ions, such as Li, during the charging and discharging process. The molar content of active ions, such as Li, is different when the battery is discharged to different states. In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Li will change after the charge and discharge cycle.

[0193] In the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0194] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0195] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0196] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0197] [Electrolytes]

[0198] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0199] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0200] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0201] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0202] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0203] [Isolation film]

[0204] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0205] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0206] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0207] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0208] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0209] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 7 The battery cell 5 is a square structure as an example.

[0210] In some embodiments, reference Figure 8 , the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0211] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0212] Fig. 9 4 is an example of a battery module. Fig. 9 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0213] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0214] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0215] Fig.10 and Fig.11 1 is a battery pack 1 as an example. Figure 7 and Figure 8 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0216] In addition, the second aspect of the present application further provides an electrical device, the electrical device comprising the secondary battery of each of the above embodiments. The secondary battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0217] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0218] Fig.12 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0219] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.

[0220] Example

[0221] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0222] The materials used in the examples of the present application are prepared by the following process.

[0223] Preparation of material 1-1:

[0224] The flake graphite is mechanically crushed, and the volume distribution particle size Dv50 after spheroidization is 12μm, and then purified to obtain natural spherical graphite. The obtained natural spherical graphite is mixed with filler petroleum asphalt (the softening point of petroleum asphalt is 110°C) in a ratio of 100:22, and then the mixed material is placed in a device that can perform programmed temperature increase, heated to 200°C and kept warm for 1h, and then continued to heat to 700°C and kept warm for 1h, and then cooled to room temperature after the end to obtain an intermediate. The obtained intermediate is placed in a graphitization furnace and subjected to graphitization heat treatment at 2510°C. After the end, it is demagnetized and sieved. The obtained material and asphalt are mixed in a ratio of 100:15 and heat treated at 1100°C to obtain material 1-1 with a coating layer. Material 1-1 satisfies: S2 / S1=15, volume distribution particle size Dv50=12.0μm, specific surface area BET=2.0m 2 / g and degree of graphitization = 96.8%.

[0225] Preparation of materials 1-2 to 1-6:

[0226] The preparation methods of materials 1-2 to 1-6 are similar to those of material 1-1, except that the volume distribution particle size Dv50 of the natural spherical graphite is adjusted to obtain materials 1-2 to 1-6. The details are as follows:

[0227] Table 1.

[0228]

[0229] Preparation of Material 2-1:

[0230] Needle coke is used as raw material, crushed by roller mill, and shaped by shaping machine. Petroleum asphalt is used as binder to granulate the shaped raw material. Then graphitization is carried out at 3000°C to obtain artificial graphite material 2-1 as secondary particles of the second carbon-based material. The volume distribution particle size (of secondary particles) of material 2-1 is Dv50=14.5, and the degree of graphitization is 94.3%.

[0231] Preparation of materials 2-2 to 2-6:

[0232] The preparation method of materials 2-2 to 2-6 is similar to that of material 2-1, except that the granulation time is adjusted to obtain materials 2-2 to 2-6.

[0233] The details are as follows:

[0234] Table 2.

[0235]

[0236] Example 1

[0237] Preparation of secondary batteries:

[0238] 1. Negative electrode sheet: The first negative electrode active material (material 1-1, as the first carbon-based material) and the second negative electrode active material (material 2-1, as the second carbon-based material) are respectively mixed with conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber in a weight ratio of 96.4:1:1.2:1.4 in an appropriate amount of solvent deionized water to form a first negative electrode slurry and a second. The second negative electrode slurry and the first negative electrode slurry are sequentially coated on the two surfaces of the negative electrode current collector copper foil in an equal mass ratio, and after drying and cold pressing, a negative electrode sheet is obtained.

[0239] 2. Positive electrode: LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523) is mixed with conductive agent carbon black (Super P) and binder polyvinylidene fluoride in a weight ratio of 96:2:2, and an appropriate amount of solvent N-methylpyrrolidone NMP is added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry is coated on both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained.

[0240] 3. Electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0241] 4. Isolation film: polypropylene film.

[0242] 5. Preparation of secondary batteries: Place the positive electrode sheet and negative electrode sheet prepared above in order, place the isolation film between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wind to obtain an electrode assembly; place the electrode assembly in an outer package, inject electrolyte after drying, and obtain a secondary battery after vacuum packaging, standing, forming, shaping and other processes.

[0243] Embodiments 2 to 6

[0244] A secondary battery was prepared in a similar manner to Example 1. The difference was that the volume distribution particle size Dv50 of the first carbon-based material was different.

[0245] Comparative Example 1

[0246] A battery was prepared in a similar manner to Example 1. The difference was that the volume distribution particle size Dv50 of the first carbon-based material was greater than 15 μm.

[0247] Performance Testing

[0248] 1. Material testing

[0249] The S2 / S1 of the first carbon-based material is obtained by testing using the following method.

[0250] The sample preparation binder and the first carbon-based material powder are mixed evenly and then applied to the copper foil, dried at 60°C for 30 minutes for use; 5 samples to be tested are cut into 6mm×6mm sizes at 5 different positions and respectively pasted on the sample stage of the CP type argon ion cross-section polisher; the samples are cut using a plasma beam to obtain the cross section of each sample. The test instrument can be the IB-09010 CP type argon ion cross-section polisher of Japan JEOL Company.

[0251] The cross sections of each sample of the first carbon-based material are scanned using a scanning electron microscope, and a scanned image is obtained by arbitrarily selecting an area in each cross section of the sample. The test may refer to JY / T010-1996. The test instrument may be a Sigma 300 scanning electron microscope from the German ZEISS company.

[0252] Randomly select cross sections of 20 particles of the first carbon-based material from the scanned image. The area formed by extending 0.25 μm from the particle surface of the first carbon-based material to the inside of the particle is recorded as the external area, and the area inside the external area is recorded as the internal area. Use image processing software to obtain the total pore area S1' of the external area of ​​each particle cross section and the pore area S2' of the internal area of ​​the first carbon-based material, and calculate the value of S2' / S1'; and calculate the arithmetic mean of S2' / S1' of all 20 particles as the value of S2 / S1 of the first carbon-based material. The image processing software can be AVIZO.

[0253] 2. Battery performance test

[0254] (1) Cycle performance test of secondary batteries

[0255] At 45°C, the prepared secondary battery was charged at a constant current of 1C to an upper cut-off voltage (corresponding to 100% SOC), then charged at a constant voltage to a current of 0.05C, and after standing for 5 minutes, the secondary battery was discharged at a constant current of 1C to a lower cut-off voltage (corresponding to 0% SOC), and the discharge capacity at this time was recorded, which was the discharge capacity of the first cycle. The secondary battery was subjected to a cyclic charge and discharge test according to the above method, and the discharge capacity after each cycle was recorded.

[0256] Capacity retention rate (%) of secondary battery after 1000 cycles at 45° C.=discharge capacity after 1000 cycles / discharge capacity at the first cycle×100%.

[0257] (2) Storage performance test of secondary batteries

[0258] At 25°C, the secondary battery prepared above was charged to 4.3V at a constant current of 1C, and then charged to a current of 0.05C at a constant voltage. After standing for 5 minutes, the secondary battery was discharged to 2.8V at a constant current of 1C, and the discharge capacity at this time was recorded, which was the discharge capacity before storage.

[0259] At 25°C, the secondary battery prepared above was charged to 4.3V at 1C constant current, and then charged to 0.05C at constant voltage. The secondary battery was then stored in a 60°C constant temperature box for 180 days. Capacity retention rate (%) of the secondary battery stored at 60°C for 180 days = discharge capacity after storage / discharge capacity before storage × 100%.

[0260] (3) Dynamic test of secondary batteries

[0261] At 25°C, the secondary battery was charged to 4.3V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage, and after standing for 5 minutes, the secondary battery was discharged to 2.8V at a constant current of 0.33C, and its actual capacity was recorded as C0.

[0262] Then the secondary battery is charged with constant current at 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0 in sequence to 4.3V or 0V negative electrode cut-off potential (whichever is reached first). After each charge, it is discharged to 2.8V at 1C0. Record the charge rate at different charge rates to 10%, 20%, 30%, etc. until 80% SOC (State of The charging rate-negative electrode potential curve under different SOC states is drawn, and the charging rate corresponding to the negative electrode potential of 0V under different SOC states is obtained after linear fitting. The charging rate is the charging window under the SOC state, which is recorded as C10%SOC, C20%SOC, C30%SOC, C40%SOC, C50%SOC, C60%SOC, C70%SOC, and C80%SOC respectively. The charging time T of the secondary battery from 10% SOC to 80% SOC (under the premise that the secondary battery does not precipitate lithium) is calculated according to the formula (60 / C20%SOC+60 / C30%SOC+60 / C40%SOC+60 / C50%SOC+60 / C60%SOC+60 / C70%SOC+60 / C80%SOC)×10%, and the unit is min. The shorter the charging time is, the better the dynamic performance of the secondary battery is.

[0263] (4) Energy density test of secondary batteries

[0264] At 25°C, charge the secondary battery at a constant current of 1 / 3C to 4.3V, then charge at a constant voltage of 4.3V to a current of 0.05C, let stand for 5 minutes, and then discharge at a constant current of 1 / 3C to 2.8V, and record the battery discharge energy at this time. The battery discharge energy divided by the battery volume is the battery volume energy density, in Wh / L.

[0265] The batteries prepared in Examples 1 to 6 and Comparative Example 1 were tested according to the above test methods (1) to (3). The negative electrode active materials used and the test results are shown in Table 4.

[0266] Table 3.

[0267]

[0268] From Table 3 above, it can be seen that as the particle size of the first carbon-based material decreases, the charging time gradually shortens, indicating that the kinetic performance gradually improves, while the cycle performance and storage performance slightly decrease. In Comparative Example 1, the particle size of the first carbon-based material is larger, the cycle performance and storage performance are better, and the kinetic performance decreases significantly.

[0269] Embodiments 7 to 11

[0270] A secondary battery was prepared in a similar manner to Example 1. The difference is that the volume distribution particle size Dv50 of the second carbon-based material was different. The batteries prepared in Example 1 and Examples 7 to 11 were tested according to the above test methods (3) to (4). The negative electrode active materials used and the test results are shown in Table 4.

[0271] Table 4.

[0272]

[0273] It can be seen from Table 3 above that as the particle size of the second carbon-based material decreases, the charging time gradually shortens, indicating that the kinetic performance gradually improves while the energy density decreases.

[0274] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A secondary battery, comprising a negative electrode plate, characterized in that: The negative electrode plate comprises a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector. The negative electrode film layer has a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, and the thickness of the negative electrode film layer is recorded as H; Among them, the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the first area of ​​the negative electrode film layer, the first area includes a first negative electrode active material, the first negative electrode active material includes a first carbon-based material, in the cross-sectional view of the first carbon-based material, the volume distribution particle size Dv50 of the first carbon-based material is recorded as D, the first carbon-based material includes an external area and an internal area located inside the external area, the external area refers to the area extending from the particle surface of the first carbon-based material to the inside of the particle by a distance of 0.25D, the total pore area of ​​the external area is recorded as S1, and the total pore area of ​​the internal area is recorded as S2, then the first carbon-based material satisfies S2>S1, and the volume distribution particle size Dv50 of the first carbon-based material is less than or equal to 15μm.

2. The secondary battery according to claim 1, wherein The volume distribution particle size Dv50 of the first carbon-based material is 7 μm-13 μm.

3. The secondary battery according to claim 1 or 2, wherein: 1.5≤S2 / S1≤500, optionally, 2.5≤S2 / S1≤450.

4. The secondary battery according to any one of claims 1 to 3, wherein: The area of ​​the pore structure in the outer region of the first carbon-based material is less than or equal to 0.15 μm 2 , can be selected to be less than or equal to 0.13μm 2 and / or, The inner region of the first carbon-based material includes at least one area greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of ​​0.15 μm 2 -2.0μm 2 The pore structure.

5. The secondary battery according to any one of claims 1 to 4, wherein: At least a portion of the surface of the first carbon-based material has a carbon coating layer.

6. The secondary battery according to any one of claims 1 to 5, wherein: The first carbon-based material includes primary particles; optionally, the primary particles account for ≥80% of the first carbon-based material.

7. The secondary battery according to any one of claims 1 to 6, wherein: The area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the second area of ​​the negative electrode film layer, the second area is arranged between the negative electrode collector and the first area, the second area includes a second negative electrode active material, and the second negative electrode active material includes a second carbon-based material; optionally, the second carbon-based material includes artificial graphite.

8. The secondary battery according to any one of claims 7, wherein The volume distribution particle size Dv50 of the first carbon-based material is smaller than the volume distribution particle size Dv50 of the second carbon-based material; Optionally, the volume distribution particle size Dv50 of the second carbon-based material is 13 μm-19 μm, and more optionally 14 μm-18 μm.

9. The secondary battery according to claim 7 or 8, wherein: The powder compaction density of the second carbon-based material under a pressure of 50000N is 1.80g / cm 3 -2.05g / cm 3 , optional 1.85g / cm 3 -2.03g / cm 3 .

10. The secondary battery according to any one of claims 7 to 9, wherein: The surface of the second carbon-based material has no coating layer.

11. The secondary battery according to any one of claims 7 to 10, wherein: The second carbon-based material includes secondary particles of artificial graphite; optionally, the secondary particles of artificial graphite account for greater than or equal to 80% of the second carbon-based material.

12. The secondary battery according to any one of claims 7 to 11, wherein: The particle size distribution of the second carbon-based material satisfies (Dv90-Dv10) / Dv50≤1.25, which can be selected as 0.90-1.

25.

13. The secondary battery according to any one of claims 7 to 12, wherein: The gram capacity of the first carbon-based material is greater than the gram capacity of the second carbon-based material; Optionally, the gram capacity of the first carbon-based material is ≥355 mAh / g, and can further be 355 mAh / g-368 mAh / g; Optionally, the gram capacity of the second carbon-based material is 350 mAh / g-365 mAh / g, and further optionally 352 mAh / g-362 mAh / g.

14. The secondary battery according to any one of claims 7 to 13, wherein: The graphitization degree of the first carbon-based material is 95.0%, optionally 95.5%-98.0%; and / or, The graphitization degree of the second carbon-based material is 90.0%-95.5%, and can be optionally 92.0%-95.5%.

15. The secondary battery according to any one of claims 7 to 14, wherein: The specific surface area of ​​the first carbon-based material is 1.0 m 2 / g-2.8m 2 / g, optional 1.3m 2 / g-2.1m 2 / g; and / or, The specific surface area of ​​the second carbon-based material is 0.8 m 2 / g-2.0m 2 / g, optional 1.1m 2 / g-1.7m 2 / g.

16. The secondary battery according to any one of claims 1 to 15, wherein: The first carbon-based material satisfies at least one of the following: (1) The first carbon-based material satisfies: (Dv90-Dv10) / Dv50≤1.40, which can be 0.90-1.40; (2) The powder compaction density of the first carbon-based material under a pressure of 50,000 N is 1.75 g / cm 3 -2.0g / cm 3 , optional 1.80g / cm 3 -1.98g / cm 3 ; (3) The tap density of the first carbon-based material is 0.90-1.30 g / cm 3 , optionally 0.95-1.25g / cm 3 ; (4) The volume distribution particle size Dv90 of the first carbon-based material is 13 μm-30 μm, optionally 16 μm-23 μm.

17. The secondary battery according to any one of claims 7 to 16, wherein: The second carbon-based material satisfies at least one of the following: (1) The tap density of the second carbon-based material is 0.85-1.25 g / cm 3 , optional: 0.90-1.15g / cm 3 ; (2) The second carbon-based material satisfies 0.050≤I D / I G ≤0.300, optionally, 0.070≤I D / I G ≤0.200, I D Indicates that the Raman spectrum is at 1350±50cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±50cm -1 The G peak intensity at .

18. The secondary battery according to any one of claims 7 to 17, wherein: The first negative electrode active material and / or the second negative electrode active material also include a silicon-based material; optionally, the mass proportion of the silicon-based material in the first negative electrode active material is less than or equal to 10%, optionally 5%-10%, and / or the mass proportion of the silicon-based material in the second negative electrode active material is less than or equal to 10%, optionally 5%-10%.

19. The secondary battery according to any one of claims 1 to 18, wherein: The negative electrode film layer satisfies at least one of the following: (1) The compaction density of the negative electrode film layer is ≤1.85 g / cm 3 , optionally 1.45-1.75 g / cm 3 ; (2) The porosity of the negative electrode film layer is 18.0%-38.0%, optionally 19.0%-34.0%; (3) The OI value of the negative electrode film layer is ≤30.0, and can be optionally 8.0-23.0; (4) The thickness of the negative electrode film layer is greater than or equal to 40 μm, and can be optionally 40 μm-140 μm.

20. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 19.

Citation Information

Patent Citations

  • Lithium ion battery composite negative electrode material and preparation method thereof

    CN102956889A

  • Negative electrode material, electrochemical device, and electronic device

    CN114556629A

  • Negative pole piece, preparation method thereof and lithium secondary battery

    CN114759157A

  • Negative electrode material and preparation method thereof, battery and electronic equipment

    CN115132997A

  • Core-shell structure micron silicon-carbon composite material and preparation method thereof, electrode and battery

    CN115188939A

Cited By

  • Negative electrode material and preparation method thereof, lithium ion battery and electric equipment

    CN121439787A

  • A negative electrode material, a preparation method thereof, a lithium ion battery and an electrical device

    CN121439787B

  • Secondary battery and electric device

    EP4787447A1